Dynamic Impact Damage of Oil and Gas Pipelines. (September 2020) - Nie, Hailiang; Ma, Weifeng; Sha, Shengyi; Ren, Junjie; Wang, Ke; Cao, Jun; Dang, Wei
Abstract: Dynamic impact damage is one of the main causes of Oil and Gas pipeline failure, but there is no systematic research method and achievement on pipeline dynamic impact damage at present. As the weak link of pipeline, girth weld is the most important research object in practical engineering application, so it is urgent to study the damage behaviour of pipeline girth weld under dynamic impact load. This paper reviews the experimental technology of split Hopkinson Pressure Bar in the field of dynamic impact mechanics, the theoretical knowledge of stress wave propagation theory, dynamic mechanics and damage mechanics, as well as the finite element simulation analysis method, explains the application of theory and technology in practical engineering, introduces the research status of mechanical behaviour of pipeline girth weld under dynamic impact load, and looks forward to the theoretical and technical trend of dynamic impact mechanics of pipeline girth weld. It lays a foundation for the dynamic impact safety evaluation and the establishment of protection system of pipeline girth weld.